Stately Palms in the grounds of the Trinidad Country Club - (:unkn) unknown (Queen's Park Hotel Co. Ltd., Trinidad, 2010)
The postcard shows a line of stately palms outside the Trinidad Country Club. Postcard no. 1.
Colour:Hues of green, pink and brown; Style; Portrait; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Palms--Trinidad and Tobago; Clubs--Trinidad and Tobago; Trinidad Country Club